A new method for converting foodwaste into pathogen free soil amendment for enhancing agricultural sustainability. (20th January 2016) - Pandey, Pramod; Lejeune, Mark; Biswas, Sagor; Morash, Daniel; Weimer, Bart; Young, Glenn
Abstract: Increasing emphasis on controlling the uses of chemical fertilizers requires identifying safe Organic Soil Amendments (OSA) to use as alternatives. Converting organic waste, such as foodwaste into an OSA can be an option. Such approaches are also an attempt to make beneficial use of the enormous amount of foodwaste generated globally. In this study we conducted a pathogen challenge to determine the inactivation of three foodborne pathogens in an OSA derived from a complex foodwaste stream. Further, the physiochemical characteristics of the OSA were assessed at pilot-scale experiments. The inactivation of three most common foodborne pathogens ( Escherichia coli O157:H7, Salmonella enterica subspecies enterica sv Typhimurium LT2, and Listeria monocytogenes ) was determined using bench-scale tests, simulating the process adopted at a pilot-scale facility. The pilot-scale facility uses three processes (enzyme digestion (55–57 °C), pasteurization (75–77 °C), and acidification treatments) for producing the OSA. In addition, the yields and nutrient characteristics of the OSA were analyzed using 16 pilot-scale batch tests. The results showed that the process adopted in this study for converting foodwaste to the OSA produced a soil amendment with non-detectable levels of E . coli O157:H7, Salmonella LT2, and L . monocytogenes. The yield of the OSA was 84–96% of the initial foodwaste inputs, and organic matter and C: N ratio of the OSA were 20–25% and 12:1, respectively. We anticipate that the results presented here will help in enhancing agricultural sustainability. Graphical abstract: